Behavioral determinants of brucellosis incidence among stockbreeders and their family members in rural area based on PRECEDE model - Hadi Alizadeh-Siuki; Hadi Tehrani; Mehdi Gholian-Aval; Hossein Ebrahimipour; Mohammad Vahedian-Shahroodi (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Brucellosis is one of the common diseases between humans and animals. The purpose of this study was to investigate behavioral determinants of brucellosis incidence among stockbreeders and their family members in a rural area based on the PRECEDE model. MATERIALS AND METHODS: This cross-sectional study was carried out among 540 stockbreeders and their family members in Northeastern Iran in 2019. Sampling was done in two stages including stratified sampling and random sampling method. Data collection was conducted by a valid and reliable questionnaire developed based on the PRECEDE model. Data were analyzed using SPSS16 through Pearson correlation coefficient, independent t-test, and ANOVA. Furthermore IBM SPSS AMOS version 20 was used for the path analysis. RESULTS: The mean age of the participants was 39.02 ± 16.41 years, of whom 53.1% and 46.9% were men and women, respectively. About 23.9% of the participants had a history of brucellosis in their families. Enabling factors were the most important determinant of self-efficacy and self-efficacy was the most important determinants of behavior. Evaluation of the chi-square indicators, chi-square ratio to degree of freedom, root mean square error of approximation, adjusted goodness of fit index, parsimony comparative fit index, comparative fit index, incremental fit index, and parsimonious normed fit index indices indicated that the model was well fitted and there was a positive and significant relationship between the predisposing, enabling, and reinforcing factors on the one hand and behavior on the other. chi-square indicators, chi-square ratio to degree of freedom, root mean square error of approximation, adjusted goodness of fit index, parsimony comparative fit index, comparative fit index, incremental fit index, and parsimonious normed fit index CONCLUSION: Designing and implementing health plans based on the PRECEDE model with more emphasis on self-efficacy as the most important behavioral determinants can bring about a positive effect on enhancing the brucellosis preventing behaviors.